Hubungan Antara Stres Dengan Penyalahgunaan Narkoba Pada Residen Di Rumah Rehabilitasi BNN Provinsi Bengkulu Tahun 2025 - Sari, Leka Julita; Handayan, Tita Septi; Aprianti, Delta (Student Scientific Journal, 2025)
In Indonesia, the number of drug addicts has increased in recent years, particularly in major cities. According to data from the United Nations Office on Drugs and Crime (UNDCP), approximately 220 million people worldwide use drugs. The objective of this study is to examine the relationship between stress and drug abuse among residents at the BNN Provincial Rehabilitation Centre in Bengkulu City in 2025. The research method used is an analytical observational study with a cross-sectional approach. The sampling technique employed is total sampling, with a sample size of 45 drug-dependent residents at the BNN Provincial Rehabilitation Centre in Bengkulu. The results of the univariate analysis showed that nearly half of the respondents (42.4%) experienced moderate stress, while the majority of respondents (53.3%) had high levels of drug abuse. The bivariate analysis revealed a significant association between stress and drug abuse among residents (p=0.002). There is a relationship between stress and drug abuse among residents at the BNN Rehabilitation Centre in Bengkulu Province in 2025. The researcher suggests that the BNN Rehabilitation Centre in Bengkulu Province develop activities for residents undergoing drug rehabilitation, as this can help residents overcome excessive boredom caused by repetitive routines.